Gender, Sport, and Higher Education: The Impact of Student -Faculty Interactions on Academic Achievement - Comeaux, Eddie; Harrison, C. Keith (My University, 2006)
This article ascertained the relationship between student athletes' gender and the impact of specific forms of student athlete-faculty interaction on academic achievement. Data were drawn from the Cooperative Institutional Research Program's 2000 Freshman Survey and 2004 Follow-Up Survey. The sample includes 2,952 student athletes attending four-year, predominantly white institutions. Females comprised 57 percent (N=I,688) of the sample and males 43 percent (N=1,264). Regression results revealed that both male and female student athletes' academic success is to some extent contingent upon the specific nature of their interaction with faculty. The findings also indicate that male and female student-athletes have minimal differences in their various forms of contact with faculty. The implications of these findings were discussed among student-athletes, faculty, and advisors in order to improve their roles in establishing meaningful relationships with female and male student athletes inside and outside the classroom.
Keywords: sex/gender; academic performance; relationship with campus